Spectroscopic evidence of large aspherical β-NAT particles involved in denitrification in the December 2011 Arctic stratosphere - Woiwode, Wolfgang; Höpfner, Michael; Bi, Lei; Pitts, Michael C.; Poole, Lamont R.; Oelhaf, Hermann; Molleker, Sergej; Borrmann, Stephan; Klingebiel, Marcus; Belyaev, Gennady; Ebersoldt, Andreas; Griessbach, Sabine; et al. (Karlsruhe, 2016)
We analyze polar stratospheric cloud (PSC) signatures in airborne MIPAS-STR (Michelson Interferometer for Passive Atmospheric Sounding – STRatospheric aircraft) observations in the spectral regions from 725 to 990 and 1150 to 1350 cm−1 under conditions suitable for the existence of nitric acid trihydrate (NAT) above northern Scandinavia on 11 December 2011. The high-resolution infrared limb emission spectra of MIPAS-STR show a characteristic “shoulder-like” signature in the spectral region around 820 cm−1, which is attributed to the ν2 symmetric deformation mode of NO3− in β-NAT. Using radiative transfer calculations involving Mie and T-Matrix methods, the spectral signatures of spherical and aspherical particles are simulated. The simulations are constrained using collocated in situ particle measurements. Simulations assuming highly aspherical spheroids with aspect ratios (AR) of 0.1 or 10.0 and a lognormal particle mode with a mode radius of 4.8 µm reproduce the observed spectra to a high degree. A smaller lognormal mode with a mode radius of 2.0 µm, which is also taken into account, plays only a minor role. Within the scenarios analyzed, the best overall agreement is found for elongated spheroids with AR = 0.1. Simulations of spherical particles and spheroids with AR = 0.5 and 2.0 return results very similar to each other and do not allow us to reproduce the signature around 820 cm−1. The observed “shoulder-like” signature is explained by the combination of the absorption/emission and scattering characteristics of large highly aspherical β-NAT particles. The size distribution supported by our results corresponds to ∼ 9 ppbv of gas-phase equivalent HNO3 at the flight altitude of ∼ 18.5 km. The results are compared with the size distributions derived from the in situ observations, a corresponding Chemical Lagrangian Model of the Stratosphere (CLaMS) simulation, and excess gas-phase HNO3 observed in a nitrification layer directly below the observed PSC. The presented results suggest that large highly aspherical β-NAT particles involved in denitrification of the polar stratosphere can be identified by means of passive infrared limb emission measurements.